Falsafat al-jamal fi al-zakharif al-'Arabiyah : Qubbat al-Sakhrah fi al-Quds inmudhajan - al-'Allan, Marwan ('Amman : Wizarat al-Thaqafah, 2015)
Qubbat al-Ṣakhrah (Mosque : Jerusalem); decoration and ornament; Islamic mosaics; Islamic architecture; Jerusalem.
Includes bibliographical references (pages 426-451).
Keywords: Qubbat al-Sakhrah (Mosque : Jerusalem); Islamic architecture -- Jerusalem; Architecture -- Aesthetics; Jerusalem -- Buildings, structures, etc